Indebtedness of Farmer Suicide Victims in Vidarbha Region of Maharashtra - N. M. Kale,; S.R.Khonde,; D.M.Mankar, (Journal of Agricultural Extension Management, 2025)
This paper examines aspects relating to the indebtedness issue of farmer suicide victims in Vidarbha. The paper discusses the indebtedness position of the victims' households according to the credit sources; analyses the average outstanding debts across land holdings; distribution of the victims according to the amount of debt and sums up the indebtedness issue of farmer suicide victims of Vidarbha region of Maharashtra and policy implications. Results reveal that majority (98.50 per cent) of the victims were found indebted and 92.00 per cent were defaulters. Over 51.50 per cent of the victims, had outstanding debt of both institutional and non-institutional credit sources, whereas 47.00 per cent were having debt of only institutional sources. Institutional credit sources used by the selected victims to fulfill their credit needs include cooperative and commercial banks, while non-institutional credit sources include friends, relatives and money lenders.